Unruptured tubal ectopic pregnancy: analysis and management - Lewis, Preeti F.; Rudrakar, Ashwini Pundlik; Bavdekar, Nitin Bhimrao; Singh, Nikita Brajkishore (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: From its indirect reference by Abulcasis and till the nineteenth century the ectopic pregnancy was known as a universally fatal accident. Many patients with early resolving ectopic pregnancies escape surgical treatment. Preservation of future fertility became possible with the introduction of conservative surgical procedures and with the use of methotrexate. Aim and objectives of the study were: to analyse the age group, gravida, risk factors, clinical presentation, treatment given and outcome of the unruptured ectopic pregnancy. Methods: We studied twenty-five women admitted to our tertiary care hospital, through emergency or outpatient department with tubal ectopic pregnancy from January 2017 through September 2021. Results: 25 cases were studied during a 5 years study period between January 2017 and September 2021 in a tertiary care hospital, Mumbai. Maximum incidence of tubal gestation occurred between the age group of 36-40 years (36%). Greater incidence was noted in multigravida accounting for 68%. Risk factors seen were advanced maternal age (36%) previous history of induced abortion (24%), previous history of abdominal or pelvic surgery in 20%. The typical triad of amenorrhoea, pain abdomen and bleeding were observed in majority of cases. Significantly a greater number of cases had ampullary pregnancy (52%), followed by cornual (24%) and fimbrial (24%). Out of 25 cases of unruptured tubal ectopic pregnancies, 68% cases were treated by purely surgical intervention while 8% cases were managed medically by methotrexate however in 24% cases, the medical treatment failed and they ended up having surgical intervention. Conclusions: In conclusion, this study showed that medical treatment of unruptured ectopic pregnancy with systemic methotrexate seems to be an option for some patients with unruptured tubal pregnancy.